INTERNATIONAL TRADE POLICIES AND ECONOMIC DEVELOPMENT - Egamberdiev Oybek Romanberdievich (Scholars Digest Publishing, 2023)
This article examines the impact of international trade policies on global economic development, with a specific focus on Uzbekistan. It analyzes the role of trade liberalization, protectionism, and regional integration in shaping economic outcomes. The study identifies challenges such as infrastructure deficits, regulatory barriers, and export diversification constraints facing Uzbekistan, and proposes strategic solutions to enhance trade policy effectiveness. By exploring these dynamics, the article aims to provide insights into how Uzbekistan can leverage international trade as a catalyst for sustainable economic growth.